Destination Marketing of Antalya City Port for Sports Organizations and Its Effect on Perceived Organizational - Ali Sevilmiş; Erkan Faruk Şirin (Pamukkale University, 2021)
The aim of this study is to examine the relationship between the image of Antalya City and destination marketing in sports organizations and satisfaction. In accordance with of this aim, the study group consists of 430 participants (n manager=4, n trainers=43, n athletes =315 and n referee=68) participating in Turkey Interuniversity Wushu Sanda and Taolu Championship between the dates of May 9 - 11, 2016, and the First International Mediterranean Wushu Championship between the dates of March 16 -21, 2017, held in Antalya city. In the study, it was revealed that the sub-dimensions of the perceived urban image significantly affect the destination marketing sub-dimensions and overall organization satisfaction in sports organizations. With this study, it is considered that perceived urban image can be a resource for forming a resource in the identification of the influences it exerts on destination marketing for sports organizations and organizational satisfaction, and sustainable plans formed in the stage of organizing this kind of activities.